2019
DOI: 10.1021/jacs.9b04706
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Computational Investigation of the Aerobic Oxidation of a Late Transition Metal-Hydride

Abstract: The rational development of homogeneous catalytic systems for selective aerobic oxidations of organics has been hampered by the limited available knowledge of how oxygen reacts with important organometallic intermediates. Recently, several mechanisms for oxygen insertion into late transition metal-hydride bonds have been described. Contributing to this nascent understanding of how oxygen reacts with metal-hydrides, a detailed mechanistic study of the reaction of oxygen with the Ir III hydride complex ( dm Pheb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 116 publications
2
36
0
Order By: Relevance
“…Interestingly, a solution of fully aerobically degraded (PNP)­IrH­(OAc) was also capable of performing DHBTA (Figures S8 and S9). This implies that the mixture of the presumed oxygenated iridium species can be revived by HBpin and reenter the catalytic cycle.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…Interestingly, a solution of fully aerobically degraded (PNP)­IrH­(OAc) was also capable of performing DHBTA (Figures S8 and S9). This implies that the mixture of the presumed oxygenated iridium species can be revived by HBpin and reenter the catalytic cycle.…”
mentioning
confidence: 66%
“…11 Interestingly, a solution of fully aerobically degraded (PNP)IrH(OAc) was also capable of performing DHBTA (Figures S8 and S9). This implies that the mixture of the presumed 25 In an experiment meant to push the limits of catalytic turnover, 200 pmol of (PNP)IrH(OAc) was added to a 200 μmol sample of 3-dimethylamino-1-propyne and HBpin (under argon, in dry C 6 D 6 ). After ca.…”
mentioning
confidence: 99%
“…Since metal-hydroperoxide (M-OOH) species have so far been proposed as intermediates in olefin oxidations to produce corresponding ketones using late-transition metal catalysts, we have employed H 2 O 2 as an oxidant instead of O 2 and HCOOH to examine the selective oxidation of StyreneS by 1. [42][43][44][45] Remarkably, AcetophS was not produced in the oxidation of StyreneS when using H 2 O 2 in the place of O 2 and HCOOH (Table S2). Therefore, we conclude that the oxidation of StyreneS performed by 1 involved the formation of Ir(EtBnS)-Cu generated by the reaction between Ir(H)-Cu and StyreneS through olefin insertion into an Ir III -H bond instead of an Ir-OOH species.…”
Section: Scheme 1 Schematic Representation Of Ir(etbns)-cu Formation mentioning
confidence: 99%
“…The Ir III complex (Phebox)­Ir­(OAc) 2 (OH 2 ) (Phebox = 2,6-bis­(4,4-dimethyloxazolinyl)-3,5-dimethylphenyl) was reported to require temperatures upward of 160 °C to activate n -octane and form an Ir III -octyl complex . In contrast to the PCP- and POCOP-ligated Ir complexes, such C–H bond activations proceed via concerted metalation–deprotonation (CMD) mechanisms, which maintain a high-valent Ir III oxidation state. CMD mechanisms for C–H activation are notable in their ability to operate under aerobic conditions. Further studies demonstrated that (Phebox)­Ir­(Octyl)­(OAc) could undergo β-hydride elimination to form (Phebox)­Ir­(H)­(OAc) and olefin and that the Ir–H product reacts with O 2 and HOAc to regenerate the starting (Phebox)­Ir­(OAc) 2 (OH 2 ) complex at moderate temperatures, establishing a potential cycle for aerobic alkane dehydrogenation. , …”
Section: Introductionmentioning
confidence: 99%